Prevalência de neoplasias em bovinos abatidos no estado de Mato Grosso - Vidotti, Milene Josyane (2022)
This dissertation aimed to study the prevalence of neoplasms in cattle slaughtered in slaughterhouses under federal and state inspection in Mato Grosso, between 2019 and 2020 and perform the histological characterization of the findings during ante-mortem and post-mortem inspection. A total of 1,536,636 cattle were slaughtered in the selected slaughterhouses. During this study, 112 samples were collected and of these 93 were considered neoplasms. For this study, the analytical observational study technique was used, and for this, meatpacking industries with federal and state inspection regime were selected, from the four main livestock regions of the State of Mato Grosso, according to the number of animals slaughtered in each region. The data obtained in this study were analyzed regarding its prevalence by sex, age, origin, type and anatomical location of the tumor. The tumors with the highest number of cases were found in the digestive system, where 26 neoplasms were registered, followed by the urinary/reproductive system (22), sist. Lymphatic (12) and respiratory (11), cardiovascular (5), indeterminate (3), integumentary (2), osteomuscular (1). Females older than 36 months were more affected, the neoplasms found were mostly malignant (90%) and of epithelial origin (62%).